Cancer Rate of the Indeterminate Lesions at Low or High Risk According to Italian System for Reporting of Thyroid FNA - Valabrega, Stefano; Santolamazza, Giuliano; Romanelli, Francesco; Scapicchio, Giorgia; D'Angelo, Francesco; Bellotti, Carlo; Aurello, Paolo; Izzo, Luciano; Giovagnoli, Maria R.; Trimboli, Pierpaolo (Frontiers in Endocrinology, 2018)
Background: Italian consensus for the classification and reporting of thyroid cytology (ICCRTC) has been used in almost all Italian institutions since 2014. High reliability of ICCRTC in classifying low and high risk indeterminate nodules (Tir 3A and Tir 3B, respectively) was demonstrated. Here we reviewed our casuistry of thyroid indeterminate lesions to analyze the histologic outcome. Methods: All lesions undergone FNA and final histology at S. Andrea Hospital of Rome after a cytologic assessment of Tir 3A and Tir 3B, according to ICCRTC, were included in the study. Results: A number of 157 indeterminate FNA was found after the introduction of ICCRTC. Of these, 75 undergone surgery and were finally included for the study. At histology we found a 33.3% of cancers and a 67.7% of benign lesions. Out of the overall series, 25 were classified as Tir 3A and 50 as Tir 3B. Cancer rate observed in Tir 3A (1/25, 4%) was significantly (p = 0.0002) lower than that of Tir 3B (24/50, 48%). No significant difference was found in age and size between the two subcategories. Conclusions: We confirm in our series that Italian consensus for the classification and reporting of thyroid cytology allows to discriminate indeterminate lesions at low and high risk of malignancy.